PEMETAAN JARINGAN SOSIAL DALAM ORGANISASI: Studi Pada Distributor Tupperware Unit Simabur Indah di Batusangkar - Siska Elasta Putri; Damsar Damsar; Bob Alfiandi (Universitas Andalas, 2018)
The problem in this study is the occurrence of sales fluctuations or instability of sales figures in the Simabur Indah Unit. The question that arises is how to map the social marketing network in the Tupperware Distributor Simabur Indah Unit and who are the actors who have high centrality in the system. The purpose of this study is to produce a mapping of the social marketing network in the Tupperware Distributor Simabur Indah Unit and to know the existence of actors who have high centrality values in the system. The analysis used consists of social network analysis that includes three things at once, namely as a theory, as a method and as a data analysis technique. The approach used is a quantitative approach with the type of descriptive research. The findings of this study are in the form of sociogram mapping of the social network marketing structure in the Tupperware Distributor Simabur Indah Unit, and the complete network obtained by using degree centrality and betweenness centrality.